2020
DOI: 10.1103/physreve.101.062604
|View full text |Cite
|
Sign up to set email alerts
|

Reverse osmotic effect in active matter

Abstract: In nonequilibrium active matter systems, a spatial variation in activity can lead to a spatial variation in concentration of active particles satisfying, at steady state, the condition nU = const [Schnitzer, Phys. Rev. E 48, 2553 (1993); Tailleur and Cates, Phys. Rev. Lett. 100, 218103 (2008)], where n is the number density and U is the active (swim) speed. We show that this condition holds even when the variation is abrupt and when thermal Brownian motion is present provided that the Péclet number is large. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…We closed the equations by setting . This approximation revealed the essential physics and is expected to have only a quantitative, not qualitative, effect on the results, as has been the case in other studies of forces in active matter (Yan & Brady 2015; Row & Brady 2020; Kjeldbjerg & Brady 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We closed the equations by setting . This approximation revealed the essential physics and is expected to have only a quantitative, not qualitative, effect on the results, as has been the case in other studies of forces in active matter (Yan & Brady 2015; Row & Brady 2020; Kjeldbjerg & Brady 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The hierarchy of equations continues with higher moments, and a truncation is necessary. We shall close here with the first two moments by setting , as this is sufficient to illustrate the basic physics as shown by Yan & Brady (2015), Row & Brady (2020) and Kjeldbjerg & Brady (2021).…”
Section: Phoretic Motion In a Bath Of Active Particlesmentioning
confidence: 98%
See 1 more Smart Citation
“…One important intrinsic length scale due to activity is the run or persistence length ℓ = 𝑈 𝑠 𝜏 𝑅 . Previous works have shown that a spatial variation in the swim speed leads to a spatial variation in the concentration (or number density) of active particles (Schnitzer 1993;Tailleur and Cates 2008;Row and Brady 2020). By tuning the swim speed distribution of ABPs confined inside the vesicle, a spherically asymmetric density distribution can emerge and lead to net motion of the vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary modes of directed transport relies on the dynamics of micro-swimmers, or self-propelled particles. A substantial body of work has demonstrated that swimmer density can be spatially modulated using asymmetric barriers [9,10], differing regions of propulsion speed [11][12][13][14], run-and-tumble dynamics [15], motility induced phase separation [16], and dynamic swimmer affinities [17]. However, there are few known mechanisms for controlling the trajectories of swimmers.…”
Section: Introductionmentioning
confidence: 99%

Snell's Law for Gliders

Ross,
Osmanović,
Brady
et al. 2021
Preprint
Self Cite